Comparison of Mahwi's and Plato's Philosophical Texts on Theology (Raparin Journal of Humanities (RJH), 2021)
This study deals with the comparison between Mahwi’s poems and Plato’s philosophical texts on theology. It draws the assimilations and the differences between both views by analyzing Mahwi’s selected poems and Plato’s selected works including; The Timaeus and The Republic. It shows how a Kurdish poet delivers a philosophical idea within his poetry, and that great poetry is often deeply philosophical. The paper also proves that there is a strong relationship between literature and philosophy. However, many do not see the correlation between them, but if we look back into history, we see that some philosophers delivered their philosophical ideas through one of the literary genres. Such as Voltaire, Friedrich Wilhelm Nietzsche, Maulana Jaladini Romi, and Plato himself at first attempted to write tragedy in verse and he was reading great Greek poetry.